Decoupling chromatin and genetic effects through systematic analysis of gene position - Chen, Menzies (2013)
Classic ‘position-effect’ experiments repositioned genes near telomeres to demonstrate that the epigenetic landscape can dramatically alter gene expression. Here we show that systematic gene knockout collections provide an exceptional resource for interrogating position effects, not only near telomeres but at every single genetic locus. Because a single reporter gene replaces each deleted gene, interrogating this reporter provides a sensitive probe into different chromatin environments while controlling for genetic context. Using this approach we find that, whereas replacement of yeast genes with the kanMX marker does not perturb the chromatin landscape, chromatin differences associated with gene position account for over 35% of kanMX activity. We observe distinct chromatin influences, including a Set2/Rpd3-mediated antagonistic interaction between histone H3 lysine 36 trimethylation and the Rap1 transcriptional activation site in kanMX. These findings demonstrate that chromatin regulation is not governed by a uniform ‘histone code’, but by specific interactions between chromatin and genetic factors.